Kasus Campur Tangan Orang Tua dalam Rumah Tangga Anak yang Menikah Usia Muda Di Desa Condong-Tasikmalaya: Suatu Tinjauan Hukum Islam - Yadi Fahmi Arifudin; Arief Taupiqurrohman (El 'Ailaah, 2023)
Marriage is something very sacred in Islam. In the Qur'an, Allah defines marriage as Mitsaqan Ghalidzan which means a strong agreement. In the process of marriage can not be separated from problems in the household. One of the problems that often occurs in the household is the intervention of parents. This study aims to determine: (1) the forms of parental intervention in the child's household, (2) a review of Islamic law on the forms of parental interference in the child's household. The data in this study are primary data obtained from interviews with resource persons who married at a young age and experienced parental intervention in their household. This type of research is a case study qualitative research. This research was conducted using semi-structured interview data collection techniques, so as to be able to develop answers from sources. The data analysis technique used is descriptive analysis. Based on the results of the analysis, by combining the results of interviews and theories, it is concluded that the view of Islamic law on parents who interfere in determining the place of residence for children's households is permissible